PICES Press, Vol. 23, No. 2, Summer 2015 (North Pacific Marine Science Organization (PICES), 2015)
The 2015 Inter-sessional Science Board meeting: A note from the Science Board Chairman (pp. 1-3); 2015 Symposium on “Effects of climate change on the world’s oceans” (pp. 4-7); 2015 Santos Joint BrOA and SOLAS Workshop (pp. 8-8); 2015 Santos Workshop on “Effects of climate change on the biologically-driven ocean carbon pumps” (pp. 9-11); 2015 Santos Workshop on “Upwelling systems under future climate change” (pp. 12-13); 2015 Santos Workshop on “Moving towards climate-ready fishery systems” (pp. 14-16); International Symposium on “Pacific salmon and steelhead production in a changing climate” (pp. 17-21); Mitigation of harmful algal blooms: The way forward (pp. 22-24); S-HAB contributions to FUTURE (pp. 25-27); A psychological perspective on “human well-being” (pp. 28-29); PICES calendar of events (pp-30-30); A good relationship between local communities and seafood diversity (pp. 31-31); Modeling the drift of marine debris generated by the 2011 tsunami in Japan (pp. 32-36); Opening of the Hakodate Research Center for Fisheries and Oceans (pp. 37-38); The state of the western North Pacific during the 2014/2015 cold season (pp. 39-40); The Bering Sea: Current status and recent trends (pp. 41-43); The warm Blob continues to dominate the ecosystem of the northern California Current (pp. 44-46); 2015 Pacific Ecology and Evolution Conference (pp. 47-48)